Disentangling the life-history costs of direct male-male competition and sperm production - Fatema Akhter; Megan L. Head; Michael D. Jennions; Meng-Han Joseph Chung (Evolutionary Ecology, 2026)
To achieve reproductive success, males typically invest more than their rivals to win fights and secure mating opportunities. Male-male competition can then continue after copulation as sperm competition if females mate multiply. While male reproduction often comes at the expense of other fitness-related traits (e.g., growth, immunity), the relative costs of different components of male reproduction (e.g., fighting rivals or sperm production) are unclear. Addressing this oversight is challenging due to the inherent correlation between different reproductive activities: a male must fight and mate successfully before investing in sperm competition. Here, we conducted an experiment in Gambusia holbrooki to estimate the life-history costs of different components of reproduction. To quantify the cost of male-male fighting, we compared life-history traits of males in the presence and absence of rivals. To quantify the cost of sperm investment, we compared life-history traits in males that either could or could not release sperm (following ablation surgery) when in the presence of rivals. Males that fought with rivals for eight weeks did not show reduced growth, immune response, sperm count or sperm velocity than males that had not fought rivals. Interestingly, males that fought rivals spent significantly less time following females but still made the same number of mating attempts, suggesting increased mating efficiency. Conversely, males that repeatedly ejaculated over eight weeks produced significantly fewer sperm than those that could not ejaculate because of ablation of the tip of their gonopodium. Greater past sperm investment due to the inability to ejaculate increased the time spent following females, but did not affect the number of mating attempts. Our findings show that sperm investment in the presence of rivals reduces a male’s future ability to produce sperm, whereas no life-history costs of physical fighting were detected.